Assessing the usefulness of the isotopic composition of CO2 for leakage monitoring at CO2 storage sites: A review. (June 2015) - Mayer, B.; Humez, P.; Becker, V.; Dalkhaa, C.; Rock, L.; Myrttinen, A.; Barth, J.A.C.
Highlights: Stable carbon isotopes are a suitable tracer for monitoring isotopically distinct injected CO2 . δ 13 C differences between injected CO2 and baseline C > 10‰ are desirable. δ 18 O constitutes a potential complementary tracer indicating the presence of injected CO2 . Some isotope effects during transport and reactions require further investigations. Stable carbon isotope ratios constitute a cost-effective tracer at large scale. Abstract: Geological storage of injected CO2 is a promising technology to reduce CO2 emissions into the atmosphere. Tracer methods are an essential tool to monitor CO2 plume distribution in the target formation and to enable tracking potential leakage of CO2 outside the storage reservoir. Here, we demonstrate that the isotopic composition of CO2 can serve as a suitable tracer at large CO2 injection sites provided that the injected CO2 is isotopically distinct from background CO2 sources that are usually composed of dissolved inorganic carbon, bedrock-derived carbon, and soil CO2 . Very favourable conditions for this tracer approach exist if δ 13 C values of injected CO2 are more than 10‰ different from those of baseline CO2 and other dissolved inorganic carbon species at the CCS site. In this case, changes in δ 13 C values accompanied with increasing concentrations of CO2 or DIC in samples obtained regularly at monitoring sites within or above the storage reservoir indicate arrival of injected CO2 . The proportion of injected CO2 contributing to the obtained samples can be quantified when carbon isotope fractionation effects are either negligible or thoroughly known. We point out several areas where additional detailed information on carbon isotope effects during phase change, transport and geochemical reactions is desirable to refine this tracer approach for temperature, pressure and salinity conditions relevant for CO2 storage sites. Oxygen isotope ratios of injected CO2 were not found to be a conservative tracer due to oxygen isotope exchange between CO2 and water on time scales of hours to a few days. δ 18 O measurements on CO2 and H2 O have, however, revealed pore space saturation with CO2 and hence indicate the presence of injected CO2 within CO2 storage reservoirs. We suggest that the stable isotopic composition of injected CO2 is a suitable tracer for assessing the movement and fate of injected CO2 in the target reservoir and for leakage detection at CO2 storage sites, provided that the injected CO2 is isotopically distinct from background CO2 sources. A key advantage is that this tracer approach does not depend on the co-injection of additional tracers and hence can be continuously used in large-scale commercial storage projects with CO2 injection rates exceeding 1 million tonnes per year at reasonable cost.